(untitled) (Journal of the College of Basic Education, 2025)
Vital design is a language that communicates design and an element of attraction that gives great sensory and emotional support to the recipients, because of its ability to reduce psychological stress while improving cognitive and creative functions by integrating green spaces from nature into the interior design of the recipient, taking into account the creation of design forms through which the interior designer controls to achieve the actual response and a clear sense of the place for the recipient, and the sense of creative diversity with design dimensions may increase by focusing designers on them Through the diversity of the configurations used as they represent an element on which the structure of the interior spaces is built to meet the human needs that ensure integrated and efficient performance to reach the available nature, and the interior designer takes into account the diversity of other design elements that are linked to each other without separation and through which the aesthetic of interior design technique, especially in restaurants, appears, In addition to its psychological effects and that any defect in its organization leads to the weakening of the biodesign composition, which should be studied and directed care and attention, the problem of the research study has been formulated with the following question: What are the elements of bio-design? What is the role of this design as a creative act in the interior space (for Mama Zonya Restaurant in Dubai (United Arabic UAE)? While the importance of research contributes to the statement of the concept of vital design so that it can be referred to by specialists in the field of interior design as well as because of its creative role in the interior space with the benefit of it theoretically and practically so that it can be adopted in the interior design of restaurants. While the current research aims to reveal the elements of biodesign and its creative action In the interior space (of Mama Zonya Restaurant in Dubai (United Arabic Arab Emirates). The research study also included the axes of the theoretical framework as well as research procedures, represented by the research methodology based on the descriptive analytical approach (case study) and finally the research study included the extraction of the most important results, conclusions, recommendations and future proposals.